2014
DOI: 10.1038/srep04923
|View full text |Cite|
|
Sign up to set email alerts
|

Dissecting the cell to nucleus, perinucleus and cytosol

Abstract: Cells have been described under the microscope as organelles containing cytoplasm and the nucleus. However, an unnoted structure exists between the cytoplasm and the nucleoplasm of eukaryotic cells. In addition to the nuclear envelope, there exists a perinuclear region (PNR or perinucleus) with unknown composition and function. Until now, an investigation of the role of the perinucleus has been restricted by the absence of a PNR isolation method. This manuscript describes a perinucleus isolation technique on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…3D). We do note that, as observed by other investigators (27,41,42), percentages of nuclear ICAP1 measured by fractionation were lower than those obtained by quantitative fluorescence microscopy. Nonetheless, both fluorescence microscopy and cell fractionation indicated that ICAP1 FL is more nuclear than the ICAP1 PTB domain.…”
Section: Resultsmentioning
confidence: 52%
“…3D). We do note that, as observed by other investigators (27,41,42), percentages of nuclear ICAP1 measured by fractionation were lower than those obtained by quantitative fluorescence microscopy. Nonetheless, both fluorescence microscopy and cell fractionation indicated that ICAP1 FL is more nuclear than the ICAP1 PTB domain.…”
Section: Resultsmentioning
confidence: 52%
“…There has also been a report of a highly dynamic perinuclear region of unknown composition and function which may modulate forces propagating to the nucleus (Shaiken and Opekun, 2014), but further investigation is necessary. Continued advances in mass spectrometry will help to explore the role of posttranslational modifications (e.g.…”
Section: The Road Ahead - Technology Leading the Waymentioning
confidence: 99%
“…Although the mechanisms of phagocytosis by nonprofessional phagocytes [21][22][23] as well as the ability of S. aureus to exist in multiple cellular compartments including the vacuole, lysosomes, endosomes, or cytosol has been documented 24 ; this perinuclear localization has not been previously noted. The perinuclear region, located between the cytoplasm and the nucleoplasm of the mammalian cell, has been proposed to have a role in signal transmission between cytoplasm and nucleus 25 and it would be interesting to determine whether ICSA interferes with this process. However, different organelles can be localized in the immediate vicinity of the nucleus, and further studies are needed to determine the localization of ICSA at the ultrastructural level within CRS patient tissues.…”
Section: Discussionmentioning
confidence: 99%